AESTHETICS AND ECOLOGICAL SIGNIFICANCE: A PHENOMENOLOGICAL ANALYSIS OF DEW MORPHOLOGY AND WIND INTERACTION IN THE WILD - Sofyang Daeng Kelana; Gatot Ciptadi; Aulanni’am; Bagyo Yanuwiadi; Pattasang (Antis-Publisher, 2026)
Objective: This study aims to analyze the correlation between the morphological characteristics of dewdrops—specifically their shape, spatial distribution, and optical properties—and prevailing meteorological conditions to establish a basis for natural weather prediction. Method: The methodology involves the systematic observation of dew formation on various foliar surfaces, such as grass tips and leaf blades, while monitoring variables including wind velocity, solar intensity, and cloud cover. Results: The findings indicate that high wind speeds cause dewdrops to adopt a predominantly pointed morphology, oriented toward the wind direction at the leaf apex. Conversely, the anticipation of a high-temperature day is signaled by perfectly spherical dewdrops exhibiting a brilliant light mirage effect, complemented by the presence of